BMM87 bearing load on a brass pin with aluminium plates - Mohd Nur Hilmi, Mohd Nazih (2012)
The investigation is about the bearing load on a brass pin joined with Aluminium thin plates of variables thickness. The experiment had done using various dimensions of the specimens which is pin diameter, plates thickness and plate thickness to diameter ratio, t/D. The specimens were tested using universal tensile testing machine. The movement for upper crosshead of the testing machine is stopped when the specimen is break. For each specimen, the bearing load was taken and determined from the load vs. displacement graph which is obtained from the Trapezium software in computer that connects with the universal tensile testing machine. The differences dimensions of the specimens give different value of bearing load. By t/D ratio increasing, the higher load pin can support. The higher bearing load is obtained from 5mm brass pin diameter which is 3898.84 N. The finite element analysis ALGOR is use to compare the bearing stress value with experimental test, to choose the more accurate method for other investigation. Finally, the graph of bearing load vs. pin diameter can be used to design brass rivet in the future.